Divorce Pandemic Rate During the Covid-19 - Isra Patamani (Universitas Negeri Gorontalo, 2022)
The purpose of this writing is to find out the reasons for the decline of divorce during the COVID-19 pandemic and find out what efforts will be made to overcome divorce cases during the COVID-19 pandemic in the Gorontalo religious courts. qualitative with an empirical approach. The analysis technique uses a quality technique, namely data in the form of words obtained from the interview, and other documents. The result of the author is that religious courts carry out the same regulations as in courts of other regions, using mediators, access reduced by the government, the intensity of meetings between husband and wife, and the process of registration of divorce trials is completely changed with the IT system. Other efforts that can be done to minimize divorce during the Covid-19 pandemic that may be considered quite difficult, such as understanding each other, talking about wise solutions in an unemotional way, and respecting opinions that differ from other family members so as not to cause misunderstandings. And the efforts made by the Gorontalo religious court are socialization and mediation